Grammatical Interference in English Communication Used by Nurul Jadid Students - Hikmah, Durratul; Dzulqarnain, Muhammad Iskandar; Arifin, Sulton (International Journal of English Education and Linguistics (IJoEEL), 2021)
Interference is one of the factors that can undermine a language system. Generally, interference often occurs in the language learning process. The interference is caused by a tendency to accustom the pronunciation of one language to another. Its scope includes changes in sound form, grammar, sentence structure, and vocabulary. Nurul Jadid Islamic boarding school is one of the boarding schools that develops foreign language skills as an attempt to prepare young people to be able to compete in the global world. In fact, the language learners (santri) still often mix the structure of their first language into foreign languages to communicate. Therefore, this study aims to identify the grammatical interference in the foreign language communication of Nurul Jadid students, and what factors behind them. The research method used is descriptive qualitative. The results show that the form of interference in Nurul Jadid students’ communication is in the form of morphological and syntactical structures. Besides, these interferences are caused by several factors; they are learners’ bilingualism, language loyalty, synonymy necessity, and the learner’s habit in using their first language. This research is expected to provide information to language teachers so that they can find learning innovations that can improve the quality of foreign language skills of Nurul Jadid's students.